Evaluating the Opioid-Related Adverse Events of Oliceridine Versus Conventional Opioids in Patient-Controlled Analgesia After Thoracoscopic Lung Resection: A Retrospective Cohort Study - Huang C; Liu B; Xie S; Zhang Y; Liu K; Qiu Y; Wu J (Drug Design, Development and Therapy)
Chengya Huang,* Biying Liu,* Shouyu Xie, Yunyun Zhang, Kun Liu, Yuwei Qiu, Jingxiang Wu Department of Anesthesiology, Shanghai Chest Hospital, Shanghai Jiao Tong University, School of Medicine, Shanghai, 200030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingxiang Wu, Department of Anesthesiology, Shanghai Chest Hospital, Shanghai Jiao Tong University School of Medicine, No. 241 Huaihai Road West, Shanghai, People’s Republic of China, Tel +86 021-22200000-3302, Fax +86 021-32260806, Email wu_jingxiang@sjtu.edu.cnBackground: Oliceridine, a novel biased mu-opioid receptor agonist, provides analgesia comparable to morphine but with a potentially improved side effect profile. However, the comparative incidence of opioid-related adverse events (ORADEs) in patient-controlled intravenous analgesia (PCIA) remains understudied. This study aims to elucidate the differences in ORADE rates between oliceridine and conventional opioids in PCIA.Methods: We conducted a population-based retrospective cohort study at Shanghai Chest Hospital, analyzing linked healthcare data. Propensity score matching (PSM) addressed selection bias. The study included patients who received PCIA with either oliceridine or conventional opioids (sufentanil, hydromorphone and oxycodone) after thoracoscopic lung resection from January 2024 to June 2024. ORADEs assessed included postoperative nausea and vomiting (PONV), urinary retention, and opioid-induced respiratory depression (OIRD). Demographics, clinical characteristics, and outcomes within the first 24 hours post-surgery were collected.Results: From 8208 eligible patients, 3171 received oliceridine and 5037 received conventional opioids. After PSM, 2803 matched pairs were analyzed, with similar demographics and morphine equivalent doses between groups. The incidence of ORADEs was significantly lower in the oliceridine group compared to the conventional opioids group, with rates of 24.30% versus 27.83% (P < 0.01). Specifically, the oliceridine group had a reduced likelihood of PONV (15.45% vs 19.73%; Relative Risk [RR], 0.78; 95% confidence interval [CI] 0.70– 0.88; P < 0.001). No significant differences were found in OIRD or urinary retention rates.Conclusion: Oliceridine use in PCIA was associated with a lower incidence of ORADEs, primarily driven by reduced PONV, compared to conventional opioids. These findings suggest oliceridine may be a safer alternative for postoperative pain management, warranting confirmation in larger prospective randomized trials. This study is among the first to provide a comprehensive comparative analysis of ORADEs between oliceridine and conventional opioids in a real-world PCIA setting, offering valuable insights into optimizing postoperative pain management strategies.Keywords: oliceridine, patient-controlled intravenous analgesia (PCIA), opioid-related adverse events (ORADEs), postoperative nausea and vomiting (PONV)